Social Network Analysis of the Panama Papers Concentrating on the MENA Region. (24th June 2021) - Al shboul, Bashar; Rabab'ah, Abdullateef; Al-Ayyoub, Mahmoud; Jararweh, Yaser; Baker, Thar
Abstract: The release of millions of financial documents, which has been known as the 'WikiLeaks' of the financial world (a.k.a. 'Panama Papers'), has dragged global attention in how highly structured means applied by some of the elite to conceal their financial assets. Consequently, significant financial corruption allegations were raised. We concentrate on a somewhat overlooked region, the Middle East and North Africa (MENA) region. This study aims to use social network analytics to study the information contained in these documents. We are checking the major players in the MENA's trends and patterns to determine if it matches the known economic powers. The analysis reveals that while the constructed network enjoys some typical characteristics, many interesting observations and properties are worth discussing. Specifically, using the extracted network consisting of 62 987 nodes and 84 692 edges, our social network analysis finding shows that, perhaps surprisingly, the nodes or the social network are not necessarily directly correlated with perceived economic influence.